Plural linguistic biographies. Maps, stories, mixtures - Graziella Favaro (University of Bologna, 2021)
«A multiplicity of languages and cultures has entered the Italian school environment»: that is what is written in the introduction of the Indicazioni Nazionali per il curricolo della scuola dell'infanzia e del primo ciclo di istruzione (MIUR, 2012, p. 8). The ministerial document, which forms the framework for school curricula, describes the de facto multilingual situation which can be observed in all kinds of educational environments and in communities. In infancy educational services and in schools, the presence of girls and boys who practice another language at home has long been widespread and on the increase. After describing the pluralistic linguistic repertoires featured in schools, the essay presents some evidence collected in two kindergartens in Milan, as part of a training course. Teachers were invited to use a map of intra-family communication during interviews with foreign parents, in order to outline the children's language biographies, and to know the strategies and choices of the family. In the second part, the focus will be on some autobiographical fragments taken from literary texts in which the authors highlight the stages and steps they have gone through in their history of native bilinguals. Finally, a review of the legislation dealing with the themes of mother tongues, multilingualism and linguistic diversity in childcare and schools is presented.